Agenda setting and the political economy of fear: How crime news influences voters' beliefs. Issue 5 (November 2017) - Graziano, Paolo R; Percoco, Marco
In this article, we analyse the mechanisms of agenda setting by focusing on the determinants of individual attitudes towards crime and investigating the role played by the media. After a brief literature review supporting the relevance of the selected topic of inquiry and the presentation of our analytical framework, we study the persuasion effects of mass media. More specifically, we investigate how TV exposure can shape individual perceptions of specific issues such as crime, and then focus on the effects of exposure to crime news on voting decisions. Using the Italian 2001 general election as an important case study of TV power concentration, we provide evidence that media-induced agenda setting enhanced the salience of the crime issue in voters' minds during the 2001 Italian general election and contributed to the victory of the coalition led by Silvio Berlusconi. Interestingly, our results are partially driven by the switch of previous left-wing voters to voting for the centre right because of exposure to crime news.